Human Capital Formation, Foreign Direct Investment Inflows, and Economic Growth: A Way Forward to Achieve Sustainable Development - Nazish Kanval; Hajra Ihsan; Saba Irum; Iffat Ambreen (Journal of Management Practices, Humanities and Social Sciences, 2024)
This research adds to the human capital and growth debate by examining the moderating role of net foreign direct investment inflows on the impact of human capital formation on growth in Pakistan while controlling renewable energy, carbon emission, and urbanization from 1990 to 2019. Furthermore, the study aims to explore the long-run and short-run interplay between human capital, physical capital, renewable energy, carbon emission, urbanization, and economic growth. The study also provides policy implications for achieving sustainable development goals. The autoregressive distributed lag framework has been used in an attempt to achieve the desired objectives. In order to assess the short-term impacts on the underlying variables, the error correction model is computed. The long-run estimations are obtained by applying the autoregressive distributed lag methodology. The findings show that foreign direct invesment, renewable energy, physical capital, and human capital formation all have positive effects on Pakistan's economic growth over the long and short terms. Foreign direct invesment greatly increases human capital, and this promotes economic growth. At the same time, urbanization and carbon emissions have negative effects on growth over the long and short terms. The study offers policy recommendations for the stakeholders based on the empirical findings, which will support sustainable development and equitable growth. To achieve sustainable development goal 4, which aims to protect inclusive and equitable quality education and promote lifetime learning opportunities as essential for human capital development, Pakistan should prioritize investing in the development of human capital through health and education. Prioritise policies that encourage the use of renewable energy sources to lower CO2 emissions to achieve environmental sustainability and inclusive growth. The government should also put policies in place that encourage foreign direct invesment inflows. SDGs 8 and 9—decent work, economic growth, support industry, innovation, and infrastructure—can be accomplished with the aid of attracting foreign direct investment and enhancing human capital.